Associations of Salivary BPIFA1 Protein in Chronic Periodontitis Patients with Type 2 Diabetes Mellitus - Yue Guo; Lin-Na Guo; Jun-Fei Zhu; Chen-Yi Tang; Yun-Zhi Feng; Hou-De Zhou (International Journal of Endocrinology)
Aims. To explore the differences in salivary BPI fold containing family A, member 1 (BPIFA1) concentration among type 2 diabetes mellitus (T2DM) subjects with various severities of chronic periodontitis and to determine whether BPIFA1 in saliva can be used as a potential biomarker of T2DM. Methods. Unstimulated saliva samples were collected from 44 subjects with T2DM and 44 without T2DM (NDM). Additionally, demographic data and general health parameters, including fasting blood glucose (FBG) and body mass index (BMI), were collected. We also detected full-mouth clinical periodontal parameters including probing pocket depth (PPD), clinical attachment level (CAL), bleeding index (BI), and plaque index (PLI). Salivary BPIFA1, tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) concentrations were also detected. Results. BPIFA1 in saliva was detected at relatively high levels. T2DM subjects had decreased salivary BPIFA1 concentrations (P=0.031). In T2DM subjects with nonperiodontitis or severe periodontitis, the level of BPIFA1 was significantly lower compared with that of NDM. Salivary TNF-α concentration displayed a similar trend to BPIFA1 in the NDM group. Conclusions. BPIFA1 protein is rich in saliva and might be used as a potential predictive biomarker of T2DM, especially in patients with severe periodontitis and nonperiodontitis. This trial is registered with ChiCTR-ROC-17010310.